Based on mesh sensor network: design and implementation of security monitoring system with Bluetooth technology - Bilal Hashim Hameed; Anmar Yahya Taher; Raed Khalid Ibrahim; Adnan Hussein Ali; Yasser Adnan Hussein (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
One of the most critical aspects to consider in wireless sensor networks is security, particularly in internet of things (IoT) implementations. Sensor network applications had risen in the past 5 years since these networks have been used in various parts of life (smart residential and commercial buildings, medical, and agriculture). In this study, we provide a novel network of sensors based on the Bluetooth network that may be used to protect commercial buildings. The Bluetooth type HC 06 was chosen since it has a low energy consumption and a communication range of 100 meters. Such security network includes motion sensors and control cameras that are controlled by an Arduino Nano microcontroller. The motion sensor's primary characteristics are solely applicable to humans, and the Arduino Nano is an open-source microcontroller. The key benefit of this research is that it demonstrates how to create a low-cost Bluetooth sensor security network with limited storage space for control movies.